2020
DOI: 10.1002/cjce.23718
|View full text |Cite
|
Sign up to set email alerts
|

Non‐isothermal crystallization of Ziegler Natta i‐PP‐graphene nanocomposite: DSC and new model prediction

Abstract: Crystallization occurs in processing i-PP-GnP nanocomposites, and these nanocomposites have the potential to replace traditional fillers and be used to fabricate advanced materials and technology. Therefore, this subject was comprehensively investigated by applying a recent crystallization model, non-isothermal DSC experiments, Raman spectroscopy, and WAXRD. The multi-layer GnPinduced nucleation and the crystal growth rates were modelled. The overall modelling effort generated new insights, results, and explan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 67 publications
(105 reference statements)
0
3
1
Order By: Relevance
“…It was observed that the addition of GNPs did not significantly affect the X c values. The same behavior was also previously reported [54][55][56]. Theoretically, the addition of GNPs to PA6 can have two significant effects: heterogeneous nucleation, where GNPs provide sites for polymer molecules to form crystalline structures; and, physical hindrance, where GNPs can obstruct the movement of polymer molecules [57].…”
Section: Non-isothermal Crystallization Behavior Of Pa6 and Pa6/gnps ...supporting
confidence: 82%
“…It was observed that the addition of GNPs did not significantly affect the X c values. The same behavior was also previously reported [54][55][56]. Theoretically, the addition of GNPs to PA6 can have two significant effects: heterogeneous nucleation, where GNPs provide sites for polymer molecules to form crystalline structures; and, physical hindrance, where GNPs can obstruct the movement of polymer molecules [57].…”
Section: Non-isothermal Crystallization Behavior Of Pa6 and Pa6/gnps ...supporting
confidence: 82%
“…Based on Figure 1A, it is evident that the addition of nonsolvent increased the intensity of the diffraction peak at 2θ = 20.5 , whereas the addition of graphene suppressed the diffraction peak. Despite the numerous reports of the positive effect of graphene on the crystallization of polymers due to their promising nucleating agent, [65][66][67][68] the addition of 5% of graphene nanoplatelets reduced the crystallinity of PU chains in the current study.…”
Section: Xrd Analysiscontrasting
confidence: 63%
“…Our several nonisothermal crystallization publications [117][118][119][120][121][122][123] list the advantages of nonoisothermal crystallization over isothermal one and the limitations of the existing non-mechanistic empirical models contributed by Ozawa, [124] Jeziorney, [125] and Liu et al [126] Such limitations include: -Assumption of first-order crystallization rate; -Inadequacy to (i) model a single cooling rate primary and secondary crystallization experiment, and (ii) predict crystallization mechanism, crystal growth dimension, and apparent activation energy of crystallization; -Incompetence to model the effects of variable cooling rates; -Double-logarithmic data analysis which is insensitive to parametric variables; and -Use of arbitrary data-fitting empirical parameters having no physical significance. We in details derived the following, preferably called nonisothermal Avrami-Erofeev crystallization model equation, that overcomes the aforementioned limitations: [117]…”
Section: Residual Catalyst Structure and Electronic Environment With ...mentioning
confidence: 99%
“…In practice, crystallizarion occurs nonisothermally in end product fabrication. Our several nonisothermal crystallization publications [117–123] list the advantages of nonoisothermal crystallization over isothermal one and the limitations of the existing non‐mechanistic empirical models contributed by Ozawa, [124] Jeziorney, [125] and Liu et al [126] . Such limitations include:…”
Section: Polyolefin Catalyst Research In the Center For Refining And ...mentioning
confidence: 99%